Minutes (extract)
001-0110-001 Extract from Minutes of Meeting of N.C.L, 25th July 1944. 153. SPAIN: It was reported that following the issue of the National Council's Declaration on relations with Spain after the last meeting, appreciative communications had been received from Senor P. Azcarate, on behalf of Dr. Negrin, from Senor Terradez, Chairman, and Diez Torre, Secretary of the Spanish Socialist Group in Great Britain, and from a number of Members of the Parliamentary Labour Party; all of which were read and received. 292/946/1/110(i)